Crop‐to‐wild gene flow and its fitness consequences for a wild fruit tree: Towards a comprehensive conservation strategy of the wild apple in Europe. (26th December 2016) - Feurtey, Alice; Cornille, Amandine; Shykoff, Jacqui A.; Snirc, Alodie; Giraud, Tatiana
Abstract: Crop‐to‐wild gene flow can reduce the fitness and genetic integrity of wild species. Malus sylvestris, the European crab‐apple fruit tree in particular, is threatened by the disappearance of its habitat and by gene flow from its domesticated relative, Malus domestica . With the aims of evaluating threats for M. sylvestris and of formulating recommendations for its conservation, we studied here, using microsatellite markers and growth experiments: (i) hybridization rates in seeds and trees from a French forest and in seeds used for replanting crab apples in agrosystems and in forests, (ii) the impact of the level of M. domestica ancestry on individual tree fitness and (iii) pollen dispersal abilities in relation to crop‐to‐wild gene flow. We found substantial contemporary crop‐to‐wild gene flow in crab‐apple tree populations and superior fitness of hybrids compared to wild seeds and seedlings. Using paternity analyses, we showed that pollen dispersal could occur up to 4 km and decreased with tree density. The seed network furnishing the wild apple reintroduction agroforestry programmes was found to suffer from poor genetic diversity, introgressions and species misidentification. Overall, our findings indicate supported threats for the European wild apple steering us to provide precise recommendations for its conservation.